2023
DOI: 10.1371/journal.pone.0284520
|View full text |Cite
|
Sign up to set email alerts
|

Serum procalcitonin level is independently associated with mechanical ventilation and case-fatality in hospitalized COVID-19-positive US veterans–A potential marker for disease severity

Abstract: The Coronavirus-19 disease (COVID-19) has claimed over 6.8 million lives since first being reported in late 2019. The virus that causes COVID-19 disease is highly contagious and spreads rapidly. To date, there are no approved prognostic tools that could predict why some patients develop severe or fatal disease outcomes. Early COVID-19 studies found an association between procalcitonin (PCT) and hospitalization or duration of mechanical ventilation and death but were limited by the cohort sizes. Therefore, this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 95 publications
(104 reference statements)
0
3
0
Order By: Relevance
“…Some studies have found that elevated PCT levels are associated with the severity of infection, inflammatory response, and tissue damage in COVID-19 ( 33 35 ). Higher PCT levels may also indicate worsening infection and poor prognosis ( 36 , 37 ). In patients with COVID-19 infection or MI, the levels of CRP often increase ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found that elevated PCT levels are associated with the severity of infection, inflammatory response, and tissue damage in COVID-19 ( 33 35 ). Higher PCT levels may also indicate worsening infection and poor prognosis ( 36 , 37 ). In patients with COVID-19 infection or MI, the levels of CRP often increase ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…We reported that a serum PCT cut-off value of 1.2 ng/ml on admission and 0.44 ng/ml on day 5 of hospitalization predicted mortality with a sensitivity of 72.7% and 88.9% and a specificity of 78.6% and 85.7%, respectively. Jeyapalina et al [6] reported serum PCT greater than 0.20 ng/ml to be independently associated with mechanical ventilation and mortality in hospitalized COVID-19 patients (unadjusted HR, 2.28, 95%CI: 2.16-2.41 for mortality). In a meta-analysis that included patients of various severities (nonsevere and severe), the cut-off value that predicted mortality ranged from 0.05 to 0.5 ng/mL [17].…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical and laboratory parameters have been used in patients infected with SARS-CoV-2, either individually or in the form of a risk-scoring system, to predict the severity of illness, disease progression, and mortality [4,5]. Various studies have evaluated the role of serum levels of pro-calcitonin (PCT) in predicting disease severity and mortality in such patients [6][7][8]. PCT synthesis is triggered by various toxins and cytokines like interleukin-6 (IL-6) or tumor necrosis factor-alpha (TNF-ɑ).…”
Section: Introductionmentioning
confidence: 99%